The effects of high meltwater on the limnology of Lake Fryxell and Lake Hoare, Taylor Valley, Antarctica, as shown by dissolved gas, tritium and chlorofluorocarbons. Issue 4 (2nd January 2014) - Dowling, Carolyn B.; Poreda, Robert J.; Lyons, W. Berry
Abstract: Small changes in the availability of liquid water can have profound effects on the water levels, aqueous chemistry and biogeochemical dynamics of the closed-basin, perennially ice-covered lakes of the McMurdo Dry Valleys, Antarctica. We have compiled the published and unpublished data on dissolved gas, tritium and chlorofluorocarbons (CFCs) for Lake Fryxell and Lake Hoare to determine the effects of a high meltwater year (2001–02 summer) on the lakes. The dissolved gas, tritium and CFC data indicate that the pulse of freshwater that flowed onto the surfaces of the lakes did not mix extensively with the upper water column. At the bottom of Lake Hoare, the measurable CFC and lower dissolved gas values suggest that the recent meltwater may have mixed with bottom waters. The probable mechanism for this transportation is weak density currents with c . 0.1–1.5% surface water being transported downwards in Lake Hoare. This deep water input, while not constant, may have a significant effect on the chemistry of the bottom waters in Lake Hoare over time. In Lake Fryxell, the tritium and CFC data indicate that the recent meltwater did not significantly affect the bottom water chemistry; therefore, weak density currents may not be present in Lake Fryxell.